Phenomenological Exploration of Mental Health Experiences of Nursing Students in Undergoing Clinical Education - Tumiwa, Finni Fitria; Lariwu, Cicilia Karlina; Pondaa, Angelia; Sarayar, Christiane Prisilia; Pondaag, Linnie; Timbuleng, Pingkan Christy; Regar, Maria Jeinny (Media Publikasi Cendekia Indonesia, 2025)
Mental health is a critical component of overall well-being, especially for nursing students who encounter distinct academic and clinical stressors throughout their education. This study seeks to gain an in-depth understanding of nursing students' experiences during clinical practice, with a particular focus on their mental health. This study used a qualitative phenomenological approach to explore in-depth the mental health experiences of nursing students during clinical education. The study involved 15 final year nursing students who met the inclusion criteria such as being or having undergone clinical practice and being able to articulate their experiences. Data were collected through in-depth semi-structured interviews using open-ended questions and supported by observations of non-verbal responses. Data were analyzed using identification of meaningful statements, thematic grouping, and descriptive construction, while applying bracketing to minimize researcher bias. The findings identified five key themes affecting nursing students’ psychological well-being during clinical practice: psychological stress, lack of confidence and fear of mistakes, social support, coping strategies, and personal meaning of the experience. Despite facing various pressures, students were able to build mental resilience through social support and coping strategies and found positive meaning from the practice experience. Nursing educational institutions are advised to provide psychological support and stress management training to help students cope with stress during clinical practice.